Social capital, institutions and policymaking - Marco Savioli; Roberto Patuelli (Kiel Institute for the World Economy (IfW), 2016)
Economic processes, consisting of interactions between human beings, exploit the social capital of persons endowed with specific cultures, identities and education. By taking into account this complexity, the authors focus on the role of institutions and policymaking in the building of social capital and its relevance to the fulfilment of their objectives. Social capital, however, is elusive and has several dimensions with which to interpret its multifaceted functions in economics and society. The authors cannot forget that social capital is sometimes even undesirable for society, for instance when unethically used. Even so, it is widely accepted that social capital has stable and positive effects.
Keywords: Z13; B52; D78; 330; social capital; institutions; policymaker; education